A Comparison of The Nutrient Contents and In Vitro Digestibility of Silage Corn Varieties Grown as Main and Secondary Crops - Zübeyir Ağırağaç; Sezen Tayam; Mehmet Salih Kaçmaz; Sibel Erdoğan (Research in Agricultural Sciences)
A study was conducted to determine the dry matter yields as well as the nutrient compositions and in vitro digestibility of nine silage corn varieties grown as main and second crops under Van conditions. In 2020-2021, a study was conducted on 9 corn varieties from different maturation groups during the growing periods of the main crop and the second crop. The main crop was harvested during the transition from milk maturity to dough stage maturity, while the second crop was harvested at the beginning of the milk maturity period. The study determined the crude nutrient (DM, CA, CP, EE, ADF, and NDF) analysis and in vitro dry matter digestibility (IVDMD) of the corn herbage. The Bodega corn variety had the highest DM yield in the main crop, while the KxB6451 corn variety had the highest yield in the second crop. Among the varieties studied, DKC5685 had the lowest DM yield, ADF, and NDF content in the main product. However, it had the highest CP content and IVDMD (p <.05). The KxB8392 silage variety was found to have the highest CP content and digestibility compared to other varieties in the second product (p <.05). It is important to choose the most appropriate early varieties that are suitable for the ecological conditions of the region. The Capuzi variety in the main crop and the KxB8392 variety in the second crop were found to be the most suitable in terms of DM yield, CP, ADF and NDF content, and IVDMD.